2018
DOI: 10.1109/tmi.2018.2836965
|View full text |Cite
|
Sign up to set email alerts
|

A Stacked Sparse Autoencoder-Based Detector for Automatic Identification of Neuromagnetic High Frequency Oscillations in Epilepsy

Abstract: High-frequency oscillations (HFOs) are spontaneous magnetoencephalography (MEG) patterns that have been acknowledged as a putative biomarker to identify epileptic foci. Correct detection of HFOs in the MEG signals is crucial for the accurate and timely clinical evaluation. Since the visual examination of HFOs is time-consuming, error-prone, and with poor inter-reviewer reliability, an automatic HFOs detector is highly desirable in clinical practice. However, the existing approaches for HFOs detection may not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 45 publications
0
44
0
Order By: Relevance
“…(2018) employed the stacked sparse auto encoder (SSAE) to facilitate the clinical detection of HFOs in the MEG records from 20 patients with localization related epilepsy. The proposed SSAE detector also outperformed the threshold-based models by achieving 89.9% in accuracy, 88.2% in sensitivity and 91.6% in specificity 27 . The LSTM architecture is better suited for the analysis of time series data compared to other neural network architectures and the LSTM networks have been started to attract interest in the field of EEG analysis.…”
Section: Discussionmentioning
confidence: 90%
“…(2018) employed the stacked sparse auto encoder (SSAE) to facilitate the clinical detection of HFOs in the MEG records from 20 patients with localization related epilepsy. The proposed SSAE detector also outperformed the threshold-based models by achieving 89.9% in accuracy, 88.2% in sensitivity and 91.6% in specificity 27 . The LSTM architecture is better suited for the analysis of time series data compared to other neural network architectures and the LSTM networks have been started to attract interest in the field of EEG analysis.…”
Section: Discussionmentioning
confidence: 90%
“…Previous reports ( Xiang et al , 2014 ; Fedele et al , 2016 ; Migliorelli et al , 2017 ; van Klink et al , 2017 ; Guo et al , 2018 ) have shown the possibility to automatically detect HFOs, which include ripples and fast ripples, by using a set of criteria, such as amplitude and number of oscillations. However, even ripples and fast ripples are detected, it is still unclear if these detected ripples or fast ripples are pathological or physiological.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few years, an increasing body of the literature confirmed the success of feature construction using deep learning methods. Deep learning has been demonstrated to outperform traditional machine learning algorithms on numerous recognition and classification tasks [24][25][26][27][28][29], which inspires the researchers in the ASD community to apply deep learning approaches on ASD classification. Earlier, deep neural networks (DNNs) have been applied to identify ASD patients using rs-fMRI [26].…”
Section: Introductionmentioning
confidence: 99%